ENHANCING ELEMENTARY EFL LEARNERS’ UNDERSTANDING OF TIME EXPRESSIONS THROUGH INTERACTIVE WORKSHEETS - Novelia Fitriani; Angelia Margono; Masda Egy Faradilla; Siti Hamidah; Abdul Syahid; Heny Suriandari (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Understanding time concepts and their linguistic expressions remains a significant challenge for elementary EFL learners due to the lack of engaging and contextual learning materials. This Classroom Action Research aimed to enhance Grade III students’ mastery of "Telling Time" by implementing interactive, picture-based worksheets that connect abstract concepts with daily routines. The study followed the Kemmis and McTaggart model across two cycles, involving 29 participants at an elementary school in Central Kalimantan. Data collection methods included pre-tests, post-tests, classroom observations, and semi-structured interviews. The quantitative findings revealed a substantial improvement in academic performance, where the average score increased from 67 in the pre-test to 88 in the post-test, with 100% of students successfully achieving the Minimum Completion Criteria (KKM). Qualitatively, the intervention transformed the classroom dynamic from teacher-centered to student-centered, resulting in heightened motivation, reduced anxiety, and increased confidence in using English time expressions. The study concludes that utilizing visually stimulating and contextualized worksheets is highly effective in bridging the gap between abstract mathematical concepts and language application, thereby significantly boosting both cognitive comprehension and affective engagement in young learners.   ABSTRAK Memahami konsep waktu dan ekspresi linguistiknya masih menjadi tantangan signifikan bagi pembelajar EFL tingkat dasar karena kurangnya materi pembelajaran yang menarik dan kontekstual. Penelitian Tindakan Kelas ini bertujuan untuk meningkatkan penguasaan siswa kelas III dalam "Menyebutkan Waktu" dengan menerapkan lembar kerja interaktif berbasis gambar yang menghubungkan konsep abstrak dengan rutinitas sehari-hari. Studi ini mengikuti model Kemmis dan McTaggart selama dua siklus, melibatkan 29 partisipan di sebuah sekolah dasar di Kalimantan Tengah. Metode pengumpulan data meliputi pre-test, post-test, observasi kelas, dan wawancara semi-terstruktur. Temuan kuantitatif menunjukkan peningkatan substansial dalam prestasi akademik, di mana nilai rata-rata meningkat dari 67 pada pre-test menjadi 88 pada post-test, dengan 100% siswa berhasil mencapai Kriteria Penyelesaian Minimum (KKM). Secara kualitatif, intervensi tersebut mengubah dinamika kelas dari berpusat pada guru menjadi berpusat pada siswa, menghasilkan peningkatan motivasi, pengurangan kecemasan, dan peningkatan kepercayaan diri dalam menggunakan ekspresi waktu dalam bahasa Inggris. Studi ini menyimpulkan bahwa penggunaan lembar kerja yang merangsang secara visual dan kontekstual sangat efektif dalam menjembatani kesenjangan antara konsep matematika abstrak dan penerapan bahasa, sehingga secara signifikan meningkatkan pemahaman kognitif dan keterlibatan afektif pada pembelajar muda.